2006
DOI: 10.1038/nature05084
|View full text |Cite
|
Sign up to set email alerts
|

The cells and logic for mammalian sour taste detection

Abstract: Mammals taste many compounds yet use a sensory palette consisting of only five basic taste modalities: sweet, bitter, sour, salty and umami (the taste of monosodium glutamate). Although this repertoire may seem modest, it provides animals with critical information about the nature and quality of food. Sour taste detection functions as an important sensory input to warn against the ingestion of acidic (for example, spoiled or unripe) food sources. We have used a combination of bioinformatics, genetic and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
675
3
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 666 publications
(726 citation statements)
references
References 31 publications
11
675
3
12
Order By: Relevance
“…18 In addition to their neuronal actions, type III cells also respond to sour taste and carbonation. [55][56][57][58] Interestingly, data from functional magnetic resonance imaging in humans suggest carbonation attenuates brain activity in gustatory brain regions, thus reducing sweetness perception. 59 Attenuated sweetness perception may trigger sweetseeking behaviors in some individuals and may potentially increase the risk of overconsumption of high-energy foods and development of obesity.…”
Section: Taste Bud Anatomy and Physiologymentioning
confidence: 99%
“…18 In addition to their neuronal actions, type III cells also respond to sour taste and carbonation. [55][56][57][58] Interestingly, data from functional magnetic resonance imaging in humans suggest carbonation attenuates brain activity in gustatory brain regions, thus reducing sweetness perception. 59 Attenuated sweetness perception may trigger sweetseeking behaviors in some individuals and may potentially increase the risk of overconsumption of high-energy foods and development of obesity.…”
Section: Taste Bud Anatomy and Physiologymentioning
confidence: 99%
“…Although genetically distinct strains of inbred mice are known to differ in sour preference, 77 no genes have been identified that account for these differences. One candidate is the polycystic kidney disease 2-like 1 gene (Pkd2l1), which is involved in sour taste in mice 78 and possibly in humans. 79 Whether naturally occurring allelic variation in this gene is responsible for differential sour perception (in mice or humans) is not known.…”
Section: Sourness and Fermentationmentioning
confidence: 99%
“…Studies from Drosophila and the mammalian sour taste detection system also highlighted channels from the transient receptor potential (TRP) family, such as PKD2L1 and TRPA1, as sensors for acid or CO 2 [62,63] . To fully illustrate proton-sensing pathways in the brain, we will discuss some typical receptors which are directly gated or modulated by protons ( Table 2, Fig.…”
Section: Proton-sensing Pathways and Their Pathophysiological Roles Imentioning
confidence: 99%
“…Animals lacking PKD2L1-expressing cells are completely devoid of taste responses to sour stimuli [63] . A follow-up study showed that PKD2L1 is directly activated by exposure to solutions of low pH.…”
Section: Acid-sensing Receptors In Sensory System Sour Tastementioning
confidence: 99%